The ad bellum challenge of drones: Recalibrating permissible use of force - Chehtman, Alejandro Eduardo (2017)
Drones constitute an incremental advance in weapons systems. They are able to significantly reduce overall, as well as collateral, damage. These features seem to have important implications for the ad bellum permissibility of resorting to military force. In short, drones would seem to expand the right to resort to military force compared to alternative weapons systems by making resorting to force proportionate in a wider set of circumstances. This line of reasoning has significant relevance in many contemporary conflicts. This article challenges this conclusion. It argues that resorting to military force through drones in contemporary asymmetrical conflicts would usually be disproportionate. The reason for this is twofold. First, under conditions of radical asymmetry, drones may not be discriminatory enough, and, thereby, collateral damage would still be disproportionate. Second, their perceived advantages in terms of greater discrimination are counteracted by the lesser chance of success in achieving the just cause for war. As a result, resorting to military force through drones in contemporary asymmetrical conflicts would generally be disproportionate not because of the harm they would expectedly cause but, rather, because of the limited harm they are ultimately able to prevent. On the basis of normative argument and empirical data, this article ultimately shows that we need to revise our understanding of ad bellum proportionality not only at the level of moral argument but also in international law.